Actio Directa as an Element of the Polish and European System of Protection of Victims of Traffic Accidents - Wójtowicz, Ewa (Review of European and Comparative Law, 2025)
Liability insurance involves a direct claim by the injured party against the insurer (actio directa). In the case of compulsory motor insurance, it is guaranteed not only by the Polish Civil Code, but also by EU directives (currently Directive 2009/103/EC of the European Parliament and of the Council of 16 September 2009 relating to insurance against civil liability in respect of the use of motor vehicles and the enforcement of the obligation to insure against such liability). Doubtful issues related to the application of this power have repeatedly been the subject of rulings by Polish courts and statements by the doctrine. The purpose of the article is to present the nature of the actio directa and selected problems related to the application of this entitlement in practice, in particular by presenting the jurisprudence of Polish courts and the CJEU. At the same time, the article highlights the issues arising in the situation of the application of national civil liability provisions and harmonized provisions on compulsory motor vehicle insurance to this entitlement. One of the important problems is the difficulty in drawing clear boundaries between national, non-harmonized regulation, and European Union law. The research methodology used includes: analysis of the legal provisions, the caselaw of the Polish courts and CJEU as well as the views of the doctrine.